A Review on Fragmented hash based Storage techniques for Query Processing in Cloud Data Storage - Jegadeeswari, Jegadeeswari; Dinadayalan, Dinadayalan; Gnanambigai, Gnanambigai (International Journal of Computer Sciences and Engineering, 2025)
Cloud Computing is a potential paradigm employed for the deployment of applications on the Internet. Cloud is an on-demand computing service that offers a dynamic environment for the users to guarantee Quality of Service (QoS) onjjjjj’ data in cloud data centers. Security is an important role in cloud data storage while the services provided storing the data in the cloud. Most of the research works have been designed for secure cloud data storage. However, cloud users still have security issues with their outsourced data. In order to overcome such issues, we surveyed towards the fragmented hashing methods and data storage techniques in cloud. The main goal of this survey is to analysis the different method towards hashing and security methods to store data in cloud environment based on the metrics for different methods on the performance in terms of execution time and data retrieval efficiency.